CO2 Emission of Marine Transports in Batam - Singapore - Rashidi, M.; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Global warming and air pollution have become one of the important issues to the entire world community. Exhaust emissions from ships has been contributing to the health problems and environmental damage. This study focuses on the Strait of Malacca area because it is one of the world’s most congested straits used for international shipping where located on the border among three countries of Indonesia, Malaysia and Singapore. This study will predict CO2 emission from the marine transport. This is accomplished by developed a ship database in the Straits of Malacca by using the data which obtained from Automatic Identification System (AIS). From the database, MEET methodology is used to estimate the CO2 emission from ships.